Perspectives in dryland restoration: approaches for climate change adaptation - Ramón Vallejo, V.; Smanis, Athanasios; Chirino, Esteban; Ramo, V.; Fuentes, David; Valdecantos, Alejandro; Vilagrosa, Alberto (New Forests, 2012)
Reforestation efforts in dryland ecosystems frequently encounter drought and limited soil productivity, although both factors usually interact synergistically to worsen water stress for outplanted seedlings. Land degradation in drylands (e.g. desertiﬁcation) usually reduces soil productivity and, especially, soil water availability. In dry sub-humid regions, forest ﬁres constitute a major disturbance affecting ecosystem dynamics and reforestation planning. Climate change projections indicate an increase of drought and more severe ﬁre regime in many dryland regions of the world. In this context, the main target of plantation technology development is to overcome transplant shock and likely adverse periods, and in drylands this is mostly related to water limitations. In this paper, we discuss some selected steps that we consider critical for improving success in outplanting woody plants, both under current and projected climate change conditions including: (1) Plant species selection, (2) Improved nursery techniques, and (3) Improved planting techniques. The number of plant species used in reforestation is increasing rapidly, moving from a reduced set of well-known, easy-to-grow, widely used species, to a large variety of promising native species. Available technologies allow for reintroducing native plants and recovering critical ecosystem functions for many degraded drylands. However, climate change projections introduce large uncertainties about the sustainability of current reforestation practices. To cope with these uncertainties, adaptive restoration approaches are suggested, on the basis of improved plant quality, improved techniques for optimizing rain use efﬁciency in plantations, and exploring native plant species, including provenances and genotypes, for their resilience to ﬁre and water use efﬁciency.
The following values have no corresponding Zotero field: publisher: Springer Netherlands
Keywords: Mediterranean ecosystems; Nursery cultivation; Reforestation; Species selection; Water harvesting

Two provenances of Quercus ilex ssp. ballota (Desf) Samp. nursery seedlings have different response to frost tolerance and autumn fertilization - Andivia, Enrique; FERNÁNDEZ, MANUEL; VÁZQUEZ-PIQUÉ, JAVIER; Alejano, Reyes (European Journal of Forest Research, 2011)
Despite evidences that Holm oak has a high plasticity and great adaptability, there is limited or contradictory knowledge of the morphological and physiological variability of this species. Holm oak has been widely used for reforestation projects in Mediterranean areas, but has frequently shown poor ﬁeld performance. We hypothesized that Holm oak has inter-population differences in physiological responses to abiotic stressors that could affect reforestation success. The inﬂuence of nursery culture on the characteristics of Holm oaks from different provenances has not been explored in depth. Thus, we studied the effect of nursery autumn fertilization on morphological traits, frost tolerance, root growth potential, and nutritional status of two Spanish provenances of Holm oak, La Alcarria (a region with inland Mediterranean climate) and Sierra Morena Occidental (a region with a warm coastal Mediterranean climate). There were signiﬁcant differences between the provenances in frost tolerance, biomass allocation, and leaf nutrient content, suggesting a role of genetic factors. The leaves of seedlings from La Alcarria had less visual damage at -12C than seedlings from the warmer provenance (45% vs. 92%). Seedlings from La Alcarria, compared to those from Sierra Morena, had higher leaf P concentration (0.17% vs. 0.15%), greater stem diameter (3.1 mm vs. 2.7 mm), lower shoot-to-root dry mass ratio (0.46 vs. 0.53), and lower slenderness (4.03 vs. 5.31). For both provenances, N autumn fertilization improved growth, root growth potential, cold hardiness, and nutritional status of seedlings. We suggest that forest reforestation programs should consider to a greater extent Holm oak provenances and their tolerances to different abiotic stressors.
Keywords: á autumn fertilization; á reforestation á; Adaptation; adaptation á cold hardiness; Autumn fertilization; Cold hardiness; Holm oak; holm oak á provenance; provenance; Reforestation

Prospective use of collected fog water in the restoration of degraded burned areas under dry Mediterranean conditions - Estrela, María J.; Valiente, José a; Corell, David; Fuentes, David; Valdecantos, Alejandro (Agricultural and Forest Meteorology, 2009)
A mountainous plot located in the interior of the Valencia region (east coast of the Iberian Peninsula) was identiﬁed for reforestation using the fog-water collection potential prevailing in the area. Fog data were obtained by means of an instrument ensemble consisting of a passive cylindrical fog-water collector, a rain gauge, a wind direction and velocity sensor and a temperature and humidity probe. Preliminary results gave rise to the additional deployment of a low-cost 18-m2 ﬂat-panel collector connected to three 1000-l tanks for larger scale fog-water collection and storage. The 2007 annual rate of fog water that could be derived from the instrument ensemble amounted to 3.3 l/m2 /day, which turn out to ﬁll up the storage tanks completely in only 5 months, even though the ﬂat-panel collector could not be operative 100% of the time. The study made use of the in situ stored water and a micro-irrigation network to irrigate a plot of reforestation seedlings through small water pulses localized deep in the planting hole during the summer dry period. Until the present, this forest location had always shown a difﬁcult self-recovery due to the high level of land degradation resulting from recurrent forest ﬁres in the past. Results indicate that survival rates and seedling performance of the two species planted, Pinus pinaster and Quercus ilex, improved with the use of small timely waterings and additional treatments with composted biosolid.
Keywords: Micro-irrigation; passive fog collection; Reforestation; Valencia region

Prospective use of collected fog water in the restoration of degraded burned areas under dry Mediterranean conditions - Estrela, María J.; Valiente, José a.; Corell, David; Fuentes, David; Valdecantos, Alejandro (Agricultural and Forest Meteorology, 2009)
A mountainous plot located in the interior of the Valencia region (east coast of the Iberian Peninsula) was identiﬁed for reforestation using the fog-water collection potential prevailing in the area. Fog data were obtained by means of an instrument ensemble consisting of a passive cylindrical fog-water collector, a rain gauge, a wind direction and velocity sensor and a temperature and humidity probe. Preliminary results gave rise to the additional deployment of a low-cost 18-m2 ﬂat-panel collector connected to three 1000-l tanks for larger scale fog-water collection and storage. The 2007 annual rate of fog water that could be derived from the instrument ensemble amounted to 3.3 l/m2 /day, which turn out to ﬁll up the storage tanks completely in only 5 months, even though the ﬂat-panel collector could not be operative 100% of the time. The study made use of the in situ stored water and a micro-irrigation network to irrigate a plot of reforestation seedlings through small water pulses localized deep in the planting hole during the summer dry period. Until the present, this forest location had always shown a difﬁcult self-recovery due to the high level of land degradation resulting from recurrent forest ﬁres in the past. Results indicate that survival rates and seedling performance of the two species planted, Pinus pinaster and Quercus ilex, improved with the use of small timely waterings and additional treatments with composted biosolid.
Keywords: Micro-irrigation; passive fog collection; Reforestation; Valencia region

A spatial distribution model of cork oak (Quercus suber) in southwestern Spain: A suitable tool for reforestation - Hidalgo, P J; Marín, J M; Quijada, J; Moreira, J M (Forest Ecology and Management, 2008)
Cork oak (Quercus suber) is an evergreen tree characterized by a thick bark, which grows in Mediterranean schlerophyllous forests. It is most prevalent in the southwestern Iberian Peninsula. Despite the potential of the province of Huelva (southwestern Spain) to maintain mature forests of cork oak, the tree has been severely depleted and most forests have either disappeared or are seriously threatened. This paper presents a spatial distribution model of cork oak for the province of Huelva with a view to determining the optimal areas for reforestation. The model draws on all available digital cartographic information with respect to cork oak distribution: topographic data (altitude, slope and orientation) were obtained from a Digital Terrain Model (20 m scale); rainfall, temperature and PET models were based on data collected from a network of meteorological stations; litologic data derive from the litologic map of Huelva (1:100,000). The result of this work is a mesh of points at a resolution of 100 m, sufﬁcient to meet the needs of any kind of reforestation or management programmes in the area studied. Each point of this mesh contains the corresponding values for bioclimatic, topographic and litologic variables in a georeferenced data matrix. The independent variables responsible for cork oak distribution (binary dependent variables) were then identiﬁed by means of binary logistic regression analysis. North-facing slopes, abundant annual rainfall and litology were the main explaining variables. The spatial distribution model was produced by applying the formula obtained to spatial analysis software. This model is proposed as a basis for future reforestation plans, especially in those areas most affected by forest ﬁres.
Keywords: binary logistic regression; climatic modeling; Cork oak; Quercus suber; Reforestation; spatial analysis

The influence of mycorrhization with Tuber melanosporum in the afforestation of a Mediterranean site with Quercus ilex and Quercus faginea - Domínguez Núñez, José Alfonso; Serrano, Jesús Selva; Barreal, José Antonio Rodríguez; González, José Antonio Saiz De Omeñaca (Forest Ecology and Management, 2006)
A Holm oak (Quercus ilex L.) and Lusitanian oak (Quercus faginea) stand establishment, mycorrhizated with black trufﬂe (Tuber melanosporum Vitt.), situated in the north of Alicante, south-eastern Spain, was analyzed during the second year of plantation. The mycorrhization improved seedling growth, especially that of the shoots, encouraged water uptake of the seedlings during the summer drought, and improved total phosphorus absorption. Tuber melanosporum was found to colonize the roots of the seedlings very successfully
Keywords: ectomycorrhiza; Nutrients; quercus faginea lamk; Quercus ilex L; Reforestation; tuber melanosporum vitt; water stress

Drought resistance of 2-year-old saplings of Mediterranean forest trees in the field: relations between water relations, hydraulics and productivity - Gullo, M A Lo; Salleo, S; Rosso, R; Trifilo, P (Plant and soil, 2003)
Drought resistance was examined for 2-year-old saplings of Ceratonia siliqua L., Olea oleaster Hoffmgg. et Link., Quercus suber L. and Q. pubescens Willd. growing in the ﬁeld in Sicily, with the aim of testing their possible use in the reforestation of degraded areas. To this purpose, leaf conductance to water vapour (gL), transpiration rate (EL), relative water content (RWC) and water potential (L) were measured between pre-dawn and sunset, monthly from May to November. Parallel measurements of loss of hydraulic conductance of twigs of the current year (PLC) were made together with an estimate of whole-plant hydraulic conductance (KPLANT) on the basis of the ratio of maximum EL to (PD − MIN), where PD is pre-dawn L and MIN is the minimum diurnal L. C. siliqua saplings maintained high gL throughout the study period with high RWC (over 90%) and L. They grew rapidly and increased their foliage area (AL) by over 60% from May to winter rest. This was accompanied by low twig PLC (about 20% in September) resulting in high KPLANT all through the study period. In contrast, O. oleaster saplings underwent distinct dehydration in July, i.e. they showed stomatal closure due to a drop in RWC (to 75%) and L (to the turgor-loss point). This was apparently due to twig cavitation, resulting in a strong decrease of KPLANT. Plants, however, tolerated summer drought, and showed growth (AL increased by 15% from May to November). Saplings of Q. suber and Q. pubescens were much more vulnerable to twig cavitation (PLC was 35–48% from June to November) than the other two species, and their average KPLANT was lower. Saplings of Q. suber and Q. pubescens grew only during the wet spring period, and no new foliage was produced thereafter. Changes in twig hydraulic conductance played a dominant role in determining changes in KPLANT in that the two variables were well correlated to each other (r = 0.68 for P = 0.001). We conclude that C. siliqua is an ideal candidate for reforestation of Sicilian degraded areas as is O. oleaster that, however, requires some additional water supply in the summer, at least during the early years after plantation. In wetter locations of Sicily, to an altitude between 0 and 500 m, Q. suber and Q. pubescens can be used for reforestation with expected higher competitiveness of the latter over the former species.
Keywords: cavitation; Drought resistance; hydraulics; Mediterranean trees; Reforestation; water relations

EFECTOS DE DISTINTOS TRATAMIENTOS EN VIVERO EN EL ARRAIGO Y PRIMER DESARROLLO EN CAMPO DE PLANTAS DE QUERCUS SUBER L. y QUERCUS ROTUNDIFOLIA LAM .. EFECTO DEL PROTECTOR. - Suarez, M Ángeles; VÁzquez, Francisco; Baselga, Pilar; Torres, Enrique; CUEVAS, SERAFÍN (II Congreso Forestal Español, 1997)
The rootting ability and the first developes of cork oak and olm oak seedlings cultivated on different substratums and containers, as well as different harding degrees are comparied. The individual protector's effect is also analyzed.
Keywords: Cork oak; Nursery; Olm oak; Plant's production; Quercus; Reforestation

PLANTACIÓN Y SIEMBRA DE Quereus ilex L.: EFECTOS DE LA PREPARACIÓN DEL TERRENO Y DE LA UTILIZACIÓN DE PROTECTORES EN LA SUPERVIVENCIA DE PLANTAS - Ambiente, Ministerio D E Medio; NICOLÁS PERAGÓN, J L; DOMÍNGUEZ LERENA, S; HERRERO SIERRA, N; VILLAR- SALVADOR, P (II Congreso Forestal Español, 1997)
In a first experiment the effect of two tillage treatments, a deep mechanical tillage and no tillage, on the survival of seeded Quercus ilex seedlings was analysed. In a second experiment the influence of acorn seeding versus plantation of containerized seedling, as well as the effect of two types of treeshelters (with and without lateral ventilation holes) and treeshelter removal in summer on the survival of Q. ilex seedlings was studied. Microclimate inside treeshelters containing seedlings was also measured along a typical summer day. Deep tillage increased germination and survival in comparison with untilled treatment. Temperature and leaf to air vapor pressure deficit was higher inside the treeshelters, specially in those without wholes, than outside. In spite of this fact, both treeshelter types, and particularIy those with lateral ventilation holes, exhibited a higher survival percentages than the control without treeshelter. Neither acorn seeding nor the removal of treeshelters in summer improved survival. significantly.
Keywords: Acorn seeding; Holm oak; microclimate; Reforestation; Tillage

PLANTACIÓN Y SIEMBRA DE Quereus ilex L.: EFECTOS DE LA PREPARACIÓN DEL TERRENO Y DE LA UTILIZACIÓN DE PROTECTORES EN LA SUPERVIVENCIA DE PLANTAS - Ambiente, Ministerio D. E. Medio; NICOLÁS PERAGÓN, J. L.; DOMINGUEZ LERENA, S.; HERRERO SIERRA, N.; VILLAR- SALVADOR, P. (II Congreso Forestal Español, 1997)
In a first experiment the effect of two tillage treatments, a deep mechanical tillage and no tillage, on the survival of seeded Quercus ilex seedlings was analysed. In a second experiment the influence of acorn seeding versus plantation of containerized seedling, as well as the effect of two types of treeshelters (with and without lateral ventilation holes) and treeshelter removal in summer on the survival of Q. ilex seedlings was studied. Microclimate inside treeshelters containing seedlings was also measured along a typical summer day. Deep tillage increased germination and survival in comparison with untilled treatment. Temperature and leaf to air vapor pressure deficit was higher inside the treeshelters, specially in those without wholes, than outside. In spite of this fact, both treeshelter types, and particularIy those with lateral ventilation holes, exhibited a higher survival percentages than the control without treeshelter. Neither acorn seeding nor the removal of treeshelters in summer improved survival. significantly.
The following values have no corresponding Zotero field: periodical: II Congreso Forestal Español pub-location: Pamplona
Keywords: Acorn seeding; Holm oak; microclimate; Reforestation; Tillage

Los alcornocales andaluces: regeneracion y REPOBLACION ARTIFICIAL - Sánchez García, J M (Congreso Forestal Español, Lourizán - Pontevedra. 1993, 1993)
After a brief description of the types of cork tree groves that exist in Andalusia, a succint review of the way and necessary conditions in wich the restocking is done at present. Also data referring to the reforestation with Quercus suber in the last decade are collected. Finally a view of the place that the cork oak takes in the framework of the Andalusian Forestry Plan.
Keywords: Andalusian Forestry Plan; Cork Oak Forest; Reforestation; Restocking

Los alcornocales andaluces: regeneracion y REPOBLACION ARTIFICIAL - Sánchez García, J. M. (Congreso Forestal Español, Lourizán - Pontevedra. 1993, 1993)
After a brief description of the types of cork tree groves that exist in Andalusia, a succint review of the way and necessary conditions in wich the restocking is done at present. Also data referring to the reforestation with Quercus suber in the last decade are collected. Finally a view of the place that the cork oak takes in the framework of the Andalusian Forestry Plan.
The following values have no corresponding Zotero field: periodical: Congreso Forestal Español, Lourizán - Pontevedra. 1993
Keywords: Andalusian Forestry Plan; Cork Oak Forest; Reforestation; Restocking